I wonder why castles had moats : and other questions about long ago - Steele, Philip (Danbury, Connecticut : Grolier Inc, 1999)
With information and quirky facts to explain everything from 'Why did knights wear armour?' to 'Why did artist break eggs?'.
Includes index
Keywords: History